The Lecturers’ Oral Corrective Feedback Strategy in Improving Students’ Public Speaking at English Education Department: A Case Study - Khaerati, Khaerati; Bahri, Syamsul; Munawir, Ahmad; Satriani, Satriani (ETDC: Indonesian Journal of Research and Educational Review, 2025)
This research investigates lecturers’ oral corrective feedback strategies in enhancing students’ public speaking skills in the English Education Department at the Islamic University of As’adiyah Sengkang. Speaking is a crucial component in English language learning, yet many students struggle with confidence and clarity when communicating in public. Oral corrective feedback plays an essential role in guiding students to recognize and improve their speech errors during classroom interactions. The objective of this research is to identify the types of oral corrective feedback used by lecturers and analyze their impact on students’ speaking performance. This research applies a qualitative case research design, with data collected through classroom observations and interviews with both lecturers and students. The findings reveal that lecturers employ various feedback types, including recasts, elicitation, clarification requests, and metalinguistic feedback. We found that elicitation and metalinguistic feedback were the most effective in encouraging student self-correction and enhancing their engagement in public speaking tasks. The research illustrates the importance of providing clear and supportive feedback to help students overcome anxiety and build confidence in expressing ideas publicly. It also suggests that lecturers should be attentive to the way their feedback is delivered to avoid discouragement and ensure it supports language development effectively.